Respuesta :
we have
[tex]\frac{(\frac{5}{(a-3)}-4)}{(2+\frac{1}{(a-3)})}[/tex]
we know that
[tex]numerator=(\frac{5}{(a-3)}-4)[/tex]
[tex]denominator=(2+\frac{1}{(a-3)})[/tex]
Step [tex]1[/tex]
Write the numerator and denominator with a common denominator
Numerator
[tex]\frac{5}{(a-3)}-4=\frac{5-4(a-3)}{(a-3)}=\frac{(17-4a)}{(a-3)}[/tex]
Denominator
[tex](2+\frac{1}{(a-3)})=\frac{2(a-3)+1}{(a-3)}=\frac{(2a-5)}{(a-3)}[/tex]
Step [tex]2[/tex]
Divide the numerator by the denominator
[tex](\frac{(17-4a)}{(a-3)})/(\frac{(2a-5)}{(a-3)})[/tex]
To do this, multiply the numerator by the reciprocal of the denominator.
[tex](\frac{(17-4a)}{(a-3)})*(\frac{(a-3)}{(2a-5)})=\frac{(17-4a)}{(2a-5)}[/tex]
therefore
the answer is the option
Write the numerator and denominator with a common denominator. Then divide the numerator by the denominator. To do this, multiply the numerator by the reciprocal of the denominator